1985
DOI: 10.1111/j.1365-2125.1985.tb02621.x
|View full text |Cite
|
Sign up to set email alerts
|

Thrombocytopenia and leucopenia with mianserin‐dependent antibodies.

Abstract: By indirect immunofluorescence specific mianserin-dependent antibodies were detected against platelets but not against granulocytes in the serum of a patient with thrombocytopenic purpura and mild leucopenia. A complement-mediated cytotoxicity assay demonstrated 70% lysis of granulocytes but no lysis of platelets, only when mianserin was added to the medium. We suggest that, at least in some patients, mianserin may cause blood disorders by an immunologically-mediated mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1987
1987
1998
1998

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…Its side effects (Jaspan, 1986) include a hypersensitivity reaction similar to that associated with phenytoin (Dhar et al, 1974). The toxicity profile for sorbinil was similar to that observed with phenytoin in the in vitro system: the formation of a cytotoxic metabolite was only (Stricker et al, 1985). Unlike phenytoin and sorbinil, it was metabolised to a cytotoxic species by both human and murine microsomes, and was directly toxic to MNL at low concentrations (¢ 25 FLM).…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Its side effects (Jaspan, 1986) include a hypersensitivity reaction similar to that associated with phenytoin (Dhar et al, 1974). The toxicity profile for sorbinil was similar to that observed with phenytoin in the in vitro system: the formation of a cytotoxic metabolite was only (Stricker et al, 1985). Unlike phenytoin and sorbinil, it was metabolised to a cytotoxic species by both human and murine microsomes, and was directly toxic to MNL at low concentrations (¢ 25 FLM).…”
Section: Discussionmentioning
confidence: 77%
“…We have extended this system by employing human, as well as murine, microsomes in an investigation of the direct and metabolism-dependent cytotoxicity of phenytoin, sorbinil and mianserin. These drugs have been associated with a variety of adverse reactions, some of which may have an immunological aetiology (Grob & Herold, 1972;Jaspan, 1986;Stricker et al, 1985). In addition, we have attempted to define the role of metabolism in the cytotoxicity of the drugs in vitro by measurement of both stable and chemically reactive metabolites formed under the conditions of the toxicity assay.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, we have looked for irreversible binding with five drugs, amodiaquine (Larrey et al, 1986), mianserin (Stricker et al, 1985), ethinyloestradiol (Beaumont et al 1982), phenytoin (Siegal & Berkowitz, 1961) and sulphanilamide (Yamamoto & Eyanagi, 1977), which have been reported to cause adverse reactions characteristic of an immunologically mediated toxic reaction. However, it must be emphasised that the incidence, in each case, is probably less than 1 in 2000.…”
Section: Resultsmentioning
confidence: 99%
“…Agranulocytosis is the most common adverse effect associated with mianserin therapy (Chaplin, 1986) in an incidence of -1 in 10,000 (Inman, 1988), although skin rashes (Quraishy, 1981), hepatotoxicity (Urbain et al, 1984) and other blood dyscrasias have also been reported (Brogden et al, 1978). The mechanism of mianserin toxicity, however, remains to be established, although direct toxicity (O'Donnell et al, 1985) and an immunological aetiology (Stricker et al, 1985) have both been suggested. Previous in vitro studies have shown that mianserin is activated by cytochrome P-450 enzymes to a chemically reactive metabolite which readily binds to microsomal protein Lambert et al, 1988), a property shared with other antidepressants like imipramine (Kappus & Remmer, 1975) and amineptine (Geneve et al, 1987). In addition, metabolic activation may also result in the formation of a cytotoxic metabolite, although there is no simple correlation with reactive metabolite formation.…”
Section: Introductionmentioning
confidence: 99%